Effects of Some Cyanophyta Along with the Reduced Levels of Chemical Fertilizers on the Growth and Yield of Wheat - Burjus, Sanaa J.; Alsaadawi, Ibrahim S.; Janno, Francis O. (Iraqi Journal of Science, 2020)
The present work was conducted in the fields of Al-Sewarah and Kurkok stations which belong to the State Board of Agricultural Researches, Ministry of Agriculture, Iraq during the growing season of 2018. The goal of the study was to test the effects of the application of cyanobacteria (Anabaena circinalis and Nostoc commune) alone or in combination with reducing the dose of chemical fertilizers (CFs), which consisted of diammonium phosphate (DAP) and urea (46% nitrogen), on growth, yield and yield components of wheat cv. IPA99. Application of 50% and 100% of CFs without cyanobacteria as well as control (without cyanobacteria and CFs) were also included in this study for comparison.The results indicated that the use of wheat grains coated with compost amended with cyanobacteria, grains coated with compost, and foliar spray with cyanobacteria did not change yield, yield components and most of growth parameters tested in both stations. However, application of 50% CFs along with the treatments that included either the coating of grains with compost amended with cyanobacteria or the foliar spray with cyanobacteria extract resulted in grains yield, yield components, biological yield, harvest index, and test growth parameters similar to those achieved by the recommended dose of CFs. This study suggests that this approach can be applied to reduce the input of chemical fertilizers into the field and thereby reducing the cost and pollution of agroecosystem.